La brecha digital y el desarrollo humano sostenible. Propuesta de un proyecto de Telecentro en la parroquia Canchagua cantón Saquisilí provincia de Cotopaxi. - Cantuña Flores, Karla Susana (2011)
The null or deficient access to information and telecommunications services has created the existence of the Digital Divide in each of the rural and urban-marginal sectors of our country, which has prevented the achievement of Human Development and therefore the inexistence of an improvement in the quality of life of the population. This research is based on theoretical references related to the Digital Divide and Human Development. The purpose of this research is to present a strategy to reduce the Digital Divide through a Telecentre project proposal that allows the inclusion and Social Appropriation of ICTs, benefiting the inhabitants of the Canchagua parish, Saquisilí canton, Cotopaxi province, based on an infrastructure of fiber optic last mile.